Agricultural productivity, food prices and inflation in Nigeria - Mbah, Chidinma Catherine; Orjime, Simon Mtswenem; Mgbemena, Emilia M. (Journal of Management, Economics, and Industrial Organization, 2022)
Despite being an agrarian economy, Nigeria has been characterized by high food prices and inflation. This is against the expectation that in an economy where agricultural productivity is supposedly high, increased food abundance should exalt pressure on food prices, making it possible for food prices to decline, hence a decrease in inflation. To examine if agricultural productivity has any effect on food prices and if such effect transmits into inflation, time series data for Nigeria between 1981 and 2021 were used. The data were calibrated on a 3-variable structural vector autoregressive model (SVAR). Results indicated that the transmission of agricultural productivity to inflation in Nigeria is a long-run phenomenon. Increased agricultural productivity induces a positive change in food prices while an increase in food prices is accompanied by fall in inflation in the long run. The study recommends measures such as subsidization of agricultural inputs or legislation to keep input costs low so as to prevent the food prices increase that is likely to result from increased agricultural productivity due to increased production costs.
Keywords: agricultural policy; food policy; price level; money supply